Towards developing a Core Outcome Set for malnutrition intervention studies in older adults: a scoping review to identify frequently used research outcomes - Visser, M.; Mendonça, N.; Avgerinou, C.; Cederholm, T.; Cruz-Jentoft, A. J.; Goisser, S.; Kiesswetter, E.; Siebentritt, H. M.; Volkert, D.; Torbahn, G. (European Geriatric Medicine, 2022)
Purpose: To conduct a scoping review to provide a systematic overview of outcomes used in nutritional intervention studies focused on the treatment of protein-energy malnutrition in older adults. Methods: A systematic search of four electronic databases (Medline, EMBASE, CINAHL and Cochrane Central Register of Controlled Trials (CENTRAL) was performed to retrieve randomized controlled trials (RCTs), published until March 9, 2020, that evaluated the effect of nutritional interventions to treat protein-energy malnutrition in older adults and those at risk for malnutrition. Two authors screened titles, abstracts and full texts independently. One author extracted data that were cross-checked by another author. Results: Sixty-three articles reporting 60 RCTs were identified. Most frequently used outcomes included body weight/body mass index (75.0% of RCTs), dietary intake (61.7%), functional limitations (48.3%), handgrip strength (46.7%), and body circumference (40.0%). The frequencies differed by setting (community, hospital and long-term care). For some outcomes there was a preferred assessment method (e.g., Barthel index for functional limitations), while for other outcomes (e.g., functional performance) a much greater variation was observed. Conclusion: A large variation in outcomes, not only across but also within settings, was identified in nutritional intervention studies in malnourished older adults and those at risk. Furthermore, for many outcomes there was a large variation in the used assessment method. These results highlight the need for developing a Core Outcome Set for malnutrition intervention studies in older adults to facilitate future meta-analyses that may enhance our understanding on the effectiveness of treatment.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Aging; Dietary counselling; ONS; Undernutrition